2004
DOI: 10.1016/j.jmhg.2004.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Sex and gender differences in newborn infants: why are boys at increased risk?

Abstract: Newborn boys have higher morbidity and mortality than girls. Several studies have shown that male newborn sex is an independent risk factor for adverse outcome. The specific mechanisms leading to the increased risks for newborn boys are not known. However, several sex-specific reactions and physiologic responses have been described in both the fetus and newborn infants. Some of these differences persist during childhood; although later other sex and gender-specific differences become more important. Recently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 101 publications
(106 reference statements)
3
33
1
6
Order By: Relevance
“…In our study, we have found a significantly higher proportion of boys (15% more than girls) admitted to the PICU, in accord with the vast majority of the bibliography that suggested higher mortality and morbidity in boys (Balsara et al, 2013;Elsm en et al, 2004). In both cases, the median age has been around 3 years, with infants from 1 month to 2 years as the highest represented category.…”
Section: Discussionsupporting
confidence: 85%
“…In our study, we have found a significantly higher proportion of boys (15% more than girls) admitted to the PICU, in accord with the vast majority of the bibliography that suggested higher mortality and morbidity in boys (Balsara et al, 2013;Elsm en et al, 2004). In both cases, the median age has been around 3 years, with infants from 1 month to 2 years as the highest represented category.…”
Section: Discussionsupporting
confidence: 85%
“…The difference is reversed in adults, with cerebral blood flow higher in females than in males (Gur et al 1982;Rodriguez et al 1988;Gur RE and Gur RC 1990). The higher blood flow that we measured in male premature and term newborns is of particular interest because male infants are more at risk for disability, handicap, and mortality than females (Brothwood et al 1986;Elsme´n et al 2004;Mohamed and Aly 2010). In addition to higher blood flow, when comparing for gender differences, we found larger right--left asymmetry of CBF i in males than in females.…”
Section: Discussionmentioning
confidence: 58%
“…Several explanations have been proposed but are in need of further testing. In general, male fetuses and newborns are biologically more vulnerable than females [32]. Among low birth weight babies, for example, boys are more likely to suffer poor outcomes and have higher mortality rates [33].…”
Section: Child Sex Differencesmentioning
confidence: 99%